(untitled) (Third Sector Social Economic Review, 2014)
The aim of this study is to examine the reliability and validity of the Turkish translation of a commonly used scale called as Psychological Capital (developed by Luthans et.al., 2007b). The sampe is composed of 317 emloyees from different sectors and organisations. The findings indicated that the reliability coefficient for the scale is 0,97 and for the sub dimensions of the scale are 0,94, 0,87, 0,82, 0,82 for self efficacy, hope, resiliency and optimism respectively. The test-retest reliability of the factors changed between 0,82 and 0,93. To test the validity of the scale factor analysis was conducted. According to the results of the factor analysis the four-factor model measuring the self-efficacy, hope, resilience and optimism dimensions was confirmed. Ultimately, it was confirmed that the Turkish translation of the Psychological Capital Scale which was conducted on a sample being more extensive than and different with respect to sector, organisation and level from previous study (Akçay, 2012) is reliable and valid scale.